The Assistance in developing religious-based tourism villages in Susut Village, Bangli - Kadek Ayu Ekasani; I Gusti Ayu Melistyari Dewi; I Gusti Ayu Eka Suwintari; I Gusti Agung Mirah Sanjiwani; Ni Putu Isha Aprinica; I Kadek Udiyana Putra; Yudistira Zulfikri Akbar Respati; Lina Widiastuti; Shirley Maitri; Ni Kadek Yunika Rahayu (Universitas Muhammadiyah Magelang, 2021)
The natural and cultural potential of Susut Village, Banjar District is a tourist attraction that has not been fully developed by the community considering the lack of knowledge about the development of tourist villages. The purpose of this community service is to provide an understanding of the community in Susut Village, especially through village officials regarding the management of the accommodation business (home stay), assisting the registration of tourism awareness groups, and the formation of tourist villages. The knowledge and skill transfer method are used to overcome the problems experienced by village officials in Susut Village. The result of this community service is that village officials can propose pokdarwis as an institution that cares about tourism development which will eventually be able to realize the formation of a Tourism Village in Susut Village, Bangli Regency.